Food security in a changing climate : The role of cropland intensification and land acquisitions across Africa - Mechiche-Alami, Altaaf (Lund University, Faculty of Science, 2020)
Food security is one of the world’s greatest challenges. The current food system shows an entanglement across the globe which means that local farmers reliant on subsistence agriculture no longer operate in isolation of larger-scale processes within the global economy or the changing biophysical system of the planet. The persistently high number of undernourished people, volatile food prices, increasing population, expected land scarcity and negative impacts of climate change on food production all contribute to a sense of urgency that future food supply in Africa will be threatened. The current global response is increasing food production by improving the productivity of smallholders in developing countries. In recent years this has been achieved through input subsidy programs aiming at agricultural intensification and to some extent Large Scale Land Acquisitions (LSLA). This thesis investigates the challenges posed to achieving food security for all, particularly by national policies supporting LSLA and agricultural intensification programs by evaluating the local food security and environmental implications across African countries. The thesis consists of four papers framed within changes to the global food system and analyzed through the telecoupling framework. Each of the papers used separate methods, from network analysis (Paper I), GIS and probablilistic assessment (Paper II), remote sensing and residual trend analysis (Paper III) and modeling of farming systems with LPJ-GUESS (Paper IV). Paper I assesses the evolution of global LSLA by identifying three different phases (2000-2007,2008-2010,2011-2015) related to global economic changes. It shows how African lands were consistently targeted by foreign investments based on the assumption that they could improve food security in the continent and foster economic development. Paper II demonstrates that LSLA in Africa are in reality mostly targeting export markets and seldom tackle the food security needs of the countries where they occur. At the same time, they risk increasing land pressures and deforestation rates and fueling conflicts, further destabilizing food security. Paper III shows that between 2000 and 2018, only 15% of croplands in West Africa witnessed significant trends in terms of productivity. These trends were mostly attributed to climatic factors in the Sahel, but increasingly to changes in cropping practices (inputs, irrigation and land rehabilitation) throughout the region. Assuming the widespread adoption of intensification measures (elimination of fallow periods and higher fertilizer use) in North Africa, Paper IV shows that rainfed wheat yields could increase by up to 25%, but would be accompanied by dramatically higher rates of nitrogen pollution with up to a six-fold increase in leaching and seven-fold increase in N2O emissions depending on the agro-ecological zone. Finally, the thesis concludes with reflections on the dangers of prioritizing productivist policies, which I argue are unable to tackle the more pressing food accessibility issues across Africa and benefiting transnational corporations and national elites at the expense of the environment and the livelihoods of smallholder farmers. It also points to agroecology as a potential alternative for sustainably improving food security in the continent.
Keywords: Agriculture; land grabbing; sustainability science; Network Analysis; Earth observation; Crop model